2018
DOI: 10.1016/j.dental.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel magnetic nanoparticle-containing adhesive with greater dentin bond strength and antibacterial and remineralizing capabilities

Abstract: Magnetic nanoparticle-containing adhesive with DMAHDM and NACP under a magnetic force yielded much greater dentin bond strength than commercial control. The novel adhesive reduced biofilm CFU by 4 logs and increased the biofilm pH from a cariogenic pH 4.5-6.9, and therefore is promising to enhance the resin-tooth bond, strengthen tooth structures, and suppress secondary caries at the restoration margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Specimens subjected to above mentioned microorganisms exhibited different moderate antibacterial properties as demonstrated in Table 1. It can be concluded that the highest activity was attributed to the higher concentrations of iron oxide, which is in consistence with early reported research 19 …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Specimens subjected to above mentioned microorganisms exhibited different moderate antibacterial properties as demonstrated in Table 1. It can be concluded that the highest activity was attributed to the higher concentrations of iron oxide, which is in consistence with early reported research 19 …”
Section: Resultssupporting
confidence: 90%
“…This result could be owed to that the presence of iron in the ceramic matrix has increased the repulsive energy between the obtained particles, which in turn diminish their final diameters. Similar studies had revealed the effect of iron doping, addition and substitution and other transition metals on their native materials 17‐19 …”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The combination of DMAHDM, 2-methacryloyloxyethyl phosphorylcholine (MPC) and NACP was also researched [29,30,31,32,40,41,42]. MPC, one of the most common biocompatible and hydrophilic biomedical polymers, was incorporated into dentin bonding agents and composites due to its hydrophilicity that prevents the adsorption of proteins [32,33].…”
Section: Antimicrobial Applications In Dentistrymentioning
confidence: 99%